Quantifying the Peak Physical Match-Play Demands of Professional Soccer Substitutes Following Pitch-Entry: Assessing Contextual Influences - Liam Kilduff (Research Quarterly for Exercise and Sport)
Purpose: To quantify the peak post-pitch-entry physical responses of soccer substitutes while assessing contextual influences. Peak responses may be important performance indicators for substitutes introduced to provide a physical impact. Method: Thirty-three professional substitutes wore Microelectromechanical Systems during 44 matches (4 ± 3 observations·player−1). Post-pitch-entry relative peak values for total and high-speed (> 5.5 m·s−1) distances, average acceleration, and PlayerLoad™ were calculated using rolling averages over 60-s to 600-s. Linear mixed models assessed contextual influences (position, substitution timing, scoreline, and location). Results: Substitutes introduced during the final ~15 min of match-play covered less high-speed distance than first-half substitutes (~2.8–3.1 m·min−1) over 480-s to 600-s epochs, and less than 60:00–74:59 min substitutes (~1.7–1.8 m·min−1) during 540-s and 600-s epochs. Average acceleration during all except 180-s epochs was lower for 75:00+ min substitutes compared with first-half replacements (~0.27–0.43 m·s−2), and lower than 60:00–74:59 min substitutes during 60-s (~0.13 m·s−2). Substitutes introduced when their team was winning recorded greater distances over 120-s to 600-s (~6.2–7.7 m·min−1), and higher PlayerLoad™ values during 120-s, 180-s, 300-s, and 480-s epochs (~2.7–3.6 arbitrary units·min−1), compared with when scores were level at pitch-entry. Irrespective of substitution timing, substitute midfielders exceeded the total distance of substitute attackers (~5.9–16.2 m·min−1) for all except 360-s and 600-s epochs, and defenders (~13.3–26.7 m·min−1) during epochs < 300-s. Conclusions: This study provides benchmark data for practitioners tailoring training and recovery protocols, particularly “top-up” conditioning, to the competitive demands of soccer substitutes. Knowing how contextual factors influence substitutes’ peak match-play responses may help managers/coaches assess the efficacy of substitution strategies.